Integrated business projects - Olinzock, Anthony A. (South-Western Educational, 2000)
Integrated Business Projects is a fun, applications-oriented text that reinforces the major office applications found in suite software--word processing, electronic presentations, spreadsheets, and databases. The users are asked to participate in various common office careers that use these applications to show the real-world significance of learning the software